If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + -32 = 0 Reorder the terms: 2 + -32 + 3x = 0 Combine like terms: 2 + -32 = -30 -30 + 3x = 0 Solving -30 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 3x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 3x = 0 + 30 3x = 0 + 30 Combine like terms: 0 + 30 = 30 3x = 30 Divide each side by '3'. x = 10 Simplifying x = 10
| 4x+6=-22 | | 5(x-4)-6x=-24 | | x^2+5x-16=3(2x-3) | | -2=7(9+2)+3(2q-1) | | 7x+8+7x=50 | | -0.5x^2+3=-5x-2 | | 3x+4(8x-15)=10 | | -8*3+5= | | 5x-21=35 | | 7x+4=-108 | | x^3-3x^2=-3 | | 2x-x=-1 | | 12x-17=121 | | 24x^2+6=24x | | 30x+3=10-5x | | 3.1+2m=6.3 | | 0=-y+4 | | (x-2)(x+1)=2x+4x | | 7x=549 | | 12w=60 | | 4y-2y=10 | | x=-0+4 | | 60w=12 | | y=-.5+1.5x | | 4x=336 | | 16-(-5)+4= | | 3x^2-300x^2-20x+100= | | 6(y+6)+y=3(y+4)-4 | | (x-2)(x+1)=x(2)+4x | | 3x-2=-35 | | 4x+31=75 | | 16-(-5)+5= |